Science and Football VI: The Proceedings of the Sixth World Congress on Science and Football (Science and Football, 2017)
The current volume represents the proceedings of the Sixth World Congress of Science and Football. The event was held in Antalya, Turkey from 15-20 January 2007, hosted by the School of Physical Education and Sports, Ankara University in collaboration with the School of Physical Education and Sports at Middle East Technical University. The Congress continued the line of previous conferences held under the aegis of the International Steering Group on Science and Football. The series of conferences was initiated at Liverpool in 1987, later followed by meetings at Eindhoven (1991), Cardiff (1995), Sydney (1999) and Lisbon (2003). The proceedings providing a scientific record of these events have been published by E&FN Spon or by the publishers of this volume - Routledge. The Steering Group on Science and Football is one of a number affiliated to the World Commission of Science and Sports. This body is charged by the International Council for Sports Science and Physical Education (ICSSPE) with building bridges between theory and practice in specific sports. It does so by orchestrating regular conferences and a major World Congress on a four-yearly basis, co-ordinated by the relevant Steering Group and publishing the proceedings. This publication therefore is a compendium of research activities and findings which are both up to date and relevant to practice. Its usefulness is reflected in the large number of citations evident in peer-review publications within mainstream journals and the applied nature of the contents.